Identification of amino acid residues in polymerase PB2 responsible for differential replication and pathogenicity of avian influenza virus H5N1 isolated from human and cattle in Texas, US - Mahmoud Bayoumi; Ramya S. Barre; Ruby A. Escobedo; Vinay Shivanna; Nathanial Jackson; Chengjin Ye; Adolfo García-Sastre; Ahmed Mostafa; Luis Martinez-Sobrido (Emerging Microbes and Infections)
Highly pathogenic avian influenza viruses (HPAIV) pose serious public health concerns. In March 2024, a first-time outbreak of HPAIV H5N1 in dairy cattle herds was reported in the United States (US). Since then, the virus has continued to spread in cattle herds and spilt over into humans. We recently showed that the first human isolate reported in the US in Texas (HPhTX) from a dairy worker in an affected cattle farm has enhanced replication kinetics and pathogenicity in mice compared to a closely related bovine isolate (HPbTX). Herein, we show that HPhTX has enhanced polymerase activity, compared with HPbTX, in human cells and that the polymerase basic 2 (PB2) protein is the main factor responsible for this difference. Through single and combined site-directed mutagenesis and swapping the three amino acids different between HPhTX and HPbTX, we found that PB2 mutation E627K is the major contributor to the enhanced polymerase activity of HPhTX. E362G substitution in HPhTX PB2 affected the polymerase, although to a lesser extent than E627K. Moreover, M631L mutation in HPhTX PB2 enhanced polymerase activity. Rescue of a loss-of-function recombinant HPhTX (rHPhTX) containing mutations at residues 627 and 362, alone or in combination, revealed a contribution of PB2 E362G and K627E in morbidity, mortality, and viral replication as compared to rHPhTX wild-type (WT), and significantly reduced viral pathogenicity to levels comparable to rHPbTX WT. These findings indicate that HPAIV H5N1 of cattle origin has post-transmission amino acid changes that increase viral replication in human cells and pathogenicity in mice.